Combined hemophagocytic syndrome and thrombotic microangiopathy due to mixed infection with influenza virus and pneumococcal pneumonia. Issue 1 (22nd November 2018) - Ishiguro, Takashi; Kojima, Ayako; Shimizu, Taisuke; Mita, Norikatsu; Kuroiwa, Seiichiro; Takayanagi, Noboru
Key Clinical Message: Development of hemophagocytic syndrome and thrombotic microangiopathy due to community‐acquired pneumonia is rare, but delayed management of these complications can lead to a poor prognosis. Infection by both Streptococcus pneumoniae and influenza virus can cause these complications; thus, physicians should pay attention to them when treating influenza‐associated pneumococcal pneumonia. Abstract : Development of hemophagocytic syndrome and thrombotic microangiopathy due to community‐acquired pneumonia is rare, but delayed management of these complications can lead to a poor prognosis. Infection by both Streptococcus pneumoniae and influenza virus can cause these complications; thus, physicians should pay attention to them when treating influenza‐associated pneumococcal pneumonia.